Contribuição ao conhecimento químico de Cróton argyrophyllus Mull - Silva Filho, Francisco Artur e (2010)
This work reports the phytochemical investigation of the stems and roots of Croton argyrophyllus Mall (Euphorbiaceae), native from Jacobina County—BA. The chemical study of the hexane extract from the stems led to the isolation of a new crotofolane diterpene named A4,9Aio,18 -diene-5,6-oxy-[(13, 14,15, 16)-16-hydrofuran]-1- one-crotofolane (crotomicansin). From the ethanol extract, it was were isolated fl-sitosterol and stigmasterol as mixture, besides five casbane diterpenes: crotonepetin, depressin and the three new compounds, 5-hydroxy- 2Z,6E,12E-trien-4-one-casbene, 6E,12E-dien-[(1,2,3,4)-3-hydrofuran]-5-one-casbene e 1- hydroxy-2E,6Z,12E-trien-4,5-dione-casbene. The chemical prospection of the hexane extract from the roots resulted on the isolation of the triterpene acetyl aleuritolic acid (AAA), the phytosteroid spinasterol and the diterpene crotomicansin. From the ethanol extract of the roots it was possible to isolate crotomicansin epimer, 2-epi-A4'9A1°'18-diene-5, 6-oxy-[(13, 14, 15,16)- 16-hydrofuran]-1-one-crotofolane and two new crotofolane diterpenes named 16-hydroxyA4'9A1°'18-diene-5,6-oxy-[(13,14,15,16)-16-hydrofuran]-1 -one-crotofolane and its epimer 2- epi-16-hydroxy-A4'9Aio, 18-diene-5,6-oxy- [(13 , 14,15,16)-16-hydrofuran] - 1-one-crotofolane. The secondary metabolites were isolated by using conventional chromatographic methods such as: flash chromatography, filtration column chromatography, liquid-liquid partition, exclusion chromatography and high performance liquid chromatography (CLAE). Structural characterization was possible by use of spectroscopic methods including IR, 1H NMR and, mass spectrometry (EIMS and BRESIMS) 13C NMR, uni and bidimensional (HMBC, HSQC, NOESY, Sel. NOR and COSY) and comparison with literature data.